Landskap Kebahasaan Dosen Administrasi Bisnis Politeknik Negeri Sriwijaya dalam Berbagai Konteks Komunikasi: Linguistic Landscape of Business Administration Lecturers at Sriwijaya State Polytechnic in Various Communication Contexts - Sari, Luciana Lidya; Putri, Eka; Wahyuni, Sri; Meirani, Wasitoh (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the language choice patterns of Civil Servant (ASN) lecturers in the Business Administration Department of Sriwijaya State Polytechnic in various formal and informal communication contexts. This study used a qualitative descriptive method with data collection techniques through observation, questionnaire distribution, and interviews with 29 respondents. The results showed that the lecturers implemented a functional diglossia pattern by utilizing Indonesian, regional languages ??(Palembang), and foreign languages ??according to the situational context. Indonesian functions as a high code that is predominantly used in formal domains, such as lectures, academic guidance, meetings, and administrative services, with a usage rate reaching 96.5–96.55%. Conversely, situational code switching occurs to Palembang in non-formal domains, especially in casual conversations with students (55.2%) and social communication with neighbors (62.1%). This code shift aims to build familiarity, strengthen social solidarity, and strengthen cultural identity. Sociolinguistically, the lecturers' linguistic behavior demonstrates adaptive abilities to the context, interlocutors, and communication goals. This phenomenon confirms that language choice is not a random behavior, but rather the result of complex linguistic and social awareness. Thus, the linguistic practices of Polsri lecturers represent a form of functional bilingualism that balances the demands of academic professionalism and the expression of cultural identity in everyday communication within higher education settings.